1998
DOI: 10.1159/000007927
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex Virus Myelitis: Clinical Manifestations and Diagnosis by the Polymerase Chain Reaction Method

Abstract: Herpes simplex virus (HSV) myelitis has previously been reported to be a form of acute ascending necrotizing myelitis caused by HSV type 2 (HSV-2). We studied neurological symptoms, clinical course, magnetic resonance imaging (MRI) findings, and diagnosis by polymerase chain reaction (PCR) methods in 9 patients with HSV myelitis. In 6 cases, disease onset was marked by sensorimotor disturbances of lower extremities and urinary disturbances, with the transverse myelopathy gradually ascending to the cervicothora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 14 publications
1
69
0
Order By: Relevance
“…One case series reported 7 patients who developed myelitis with paraplegia or tetraplegia following acute HSV-2 infection; all were treated with antiviral therapy but only 2 made a substantial recovery. 9 Antiviral drugs are the mainstay of treating acute infections HSV-2. 10 Double-blind studies have indicated that use of antiviral drugs such as acyclovir, valacyclovir, and famciclovir moderately reduce risk of HSV-2 recurrences over a 2 to 12 month period by 43 to 59% (results statistically significant).…”
Section: Discussionmentioning
confidence: 99%
“…One case series reported 7 patients who developed myelitis with paraplegia or tetraplegia following acute HSV-2 infection; all were treated with antiviral therapy but only 2 made a substantial recovery. 9 Antiviral drugs are the mainstay of treating acute infections HSV-2. 10 Double-blind studies have indicated that use of antiviral drugs such as acyclovir, valacyclovir, and famciclovir moderately reduce risk of HSV-2 recurrences over a 2 to 12 month period by 43 to 59% (results statistically significant).…”
Section: Discussionmentioning
confidence: 99%
“…There is some similarity in both the cord appearance and delayed clinical deterioration with other insults to the spinal cord. Patients have developed similar clinical and imaging features following episodes of virally infective myelitis 14 or electric shocks. 15 …”
Section: Possible Aetiologymentioning
confidence: 99%
“…As MRI findings, spinal lesions of HSM are generally either hypointense or isointense on T1-weighted images and hyperintense on T2-weighted images similar to images obteined in HSV encephalitis (Ellie et al, 1994;Petereit et al, 1996;Nakajima et al, 1998;Kuker, et al, 1999;Galanakis et al, 2001;Gobbi et al, 2001;Azuma et al, 2001) (Fig. 1).…”
Section: Mri Findingsmentioning
confidence: 83%
“…In the past, an antiviral agent and a steroidal agent were concurrently administered in many patients. Of the 9 patients in the above mentioned study, a steroidal agent was administered concurrently: methylprednisolone pulse therapy in 4 patients, betamethasone in 2 patients and predonine in 1 patient (Nakajima et al, 1998). Regarding the use of steroids, while s t e r o i d s w e r e u s e d a f t e r c o n f i r m i n g H S M i n s o m e p a t i e n t s , t h e y w e r e a l s o u s e d i n combination with antiviral agents because of suspected demyelinating disease, such as ADEM or multiple sclerosis; autoimmune/inflammatory diseases, such as, vasculitis; or cryptogenic transverse myelopathy.…”
Section: Therapymentioning
confidence: 99%